Can vocabulary size predict narrative abilities in children with SLI? - Kambanaros, Maria; Grohmann, Kleanthes K.; Theodorou, Eleni; Michaelides, Michael (My University, 2013)
Correlating expressive vocabulary skills with narrative microstructure measures such as morphosyntactic skills revealed that both are powerful tools to assess language-impaired children. However, for expressive vocabulary to have a predictive value on narrative performance, younger children with SLI should be investigated. Our results lend support to a unified model of SLI (Rice 2003) revealing that both expressive vocabulary and narrative re-tell microstructure are delayed in school-aged Greek Cypriot children with SLI compared to their typically developing peers.
Keywords: Narrative abilities; Vocabulary size; Vocabulary skills; SLI